Trans-replicase helper activity of porcine circoviruses promotes the synergistic replication of torque teno virus - Ssemadaali, Marvin; Islam, Md-Tariqul; Fang, Wenjuan; Aboezz, Zeinab; Webb, Brett; Ramamoorthy, Sheela (Frontiers in Microbiology, 2024)
While the primary pathogenic potential of torque teno viruses (TTVs) is yet to be defined, TTVs are often co-detected with other pathogens and are suspected of exacerbating clinical disease in coinfections. Swine TTVs (TTSuVs) enhance clinical signs of porcine circovirus type 2 (PCV2) in a gnotobiotic pig model. However, the mechanisms involved are unknown. In this study, we observed that co-culture of TTSuV1 and PCV1, and specifically supplementing TTSuV1 cultures with the PCV replicase protein in trans consistently resulted in higher levels of replication of TTSuV1 when compared to TTSuV1 cultured alone. Therefore, the hypothesis that the PCV replicase (rep) protein has trans-replicase helper activity for TTSuV1 was examined. Based on EMSA and reporter gene assays, it was determined that the PCV1 rep directly interacted with the TTSuV1 UTR. The TTSuV1 rep trans-complemented a PCV rep null mutant virus, indicating that the TTSuV1 and PCV1 replicase proteins supported the replication of both viruses. In mice, the administration of plasmids This is a provisional file, not the final typeset article encoding the PCV1 rep and a TTSuV1 infectious clone resulted in the production of higher TTSuV1 genome copies in dually exposed mice when compared to singly exposed mice. Higher seroconversion and lymphoid hyperplasia were also observed in the dually exposed experimental mice. Thus, this study provides evidence for trans-replicase activity of PCVs and TTVs as a novel mechanism of explaining enhanced viral replication in coinfections involving both viruses.